Transcriptome - wide analysis of iroc target genes in the drosophila olfactory system - Taşkıran, İbrahim İhsan. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2018., 2018)
Sensing the environment is vital for an organism and it is provided by divergent sensory neurons. These neurons are generated from sensory organ precursor (SOP) cells that differentiate into neurons with diverse spectral sensitivity. The molecular mechanisms underlying neuron diversification in the olfactory system are largely unknown. Drosophila melanogaster olfactory system represents a stunning example of neuron diversification and it is an amenable system to study these mechanisms because of its reduced quantity and explicit definition. The Drosophila olfactory system comprises two olfactory organs, the antenna and maxillary palp, and 50 different olfactory receptor neuron (ORN) classes. ORNs are housed in sensilla and each sensillum contains one to four neurons. In the framework of this study we focus on homeodomain transcription factors from the TALE class, Iroquois Complex (IroC). The analysis of enhancer trap lines shows that IroC is expressed in both olfactory organs. In order to identify IroC target genes in the olfactory system, I used a genome-wide transcriptome approach and performed RNA Sequencing on antenna and maxillary palp tissue isolated from IroC triple mutant flies. I identified 11 differentially expressed OR genes and 23 transcription factors. Differentially expressed ORs were validated by qRT-PCR.
Keywords: Drosophila melanogaster.; Olfactory receptors.